Song King Connecting People, Places, and Past in Contemporary China - Gibbs, Levi S. (University of Hawaii Press, 2018)
When itinerant singers from China’s countryside become iconic artists, worlds collide. The lives and performances of these representative singers become sites for conversations between the rural and urban, local and national, folk and elite, and traditional and modern. In Song King: Connecting People, Places, and Past in Contemporary China, Levi S. Gibbs examines the life and performances of "Folksong King of Western China" Wang Xiangrong (b. 1952) and explores how itinerant performers come to serve as representative symbols straddling different groups, connecting diverse audiences, and shifting between amorphous, place-based local, regional, and national identities.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Apr 2019)
Keywords: MUSIC / Ethnomusicology; Folk singers -- China; Folk songs, Chinese -- History and criticism; Folksong; Volksmusiker; China